Swine embryo culture and transfer for export to England - James, J.E.; Reeser, P.D.; Davis, Duane L.; Straiton, E.C.; Talbot, A.C.; Polge, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A major threat to swine enterprises is the possible introduction of disease when new breeding animals are purchased and introduced. So, methods of introducing new genetic material while minimizing the potential for introducing disease are needed. Transfer of embryos from a donor sow in another herd or country would minimize disease risks. Already used to introduce new breeding stock into Specific Pathogen Free herds and other closed herds, embryos now are placed in the recipient gilt’s or sow1s uterus within a few hours after their recovery from the donor. That method prevents export and limits application of swine embryo transfer in this country, so we evaluated the feasibility of using an in vitro culture system to store embryos between donor sows and recipient females.
Keywords: Swine; Embryo; England; In vitro